Alteration of plant species assemblages can decrease the transmission potential of malaria mosquitoes. Issue 2 (14th September 2017) - Ebrahimi, Babak; Jackson, Bryan T.; Guseman, Julie L.; Przybylowicz, Colin M.; Stone, Christopher M.; Foster, Woodbridge A.
Abstract: Knowledge of the link between a vector population's pathogen‐transmission potential and its biotic environment can generate more realistic forecasts of disease risk due to environmental change. It also can promote more effective vector control by both conventional and novel means. This study assessed the effect of particular plant species assemblages differing in nectar production on components of the vectorial capacity of the mosquito Anopheles gambiae s.s ., an important vector of African malaria. We followed cohorts of mosquitoes for 3 weeks in greenhouse mesocosms holding nectar‐poor and nectar‐rich plant species by tracking daily mortalities and estimating daily biting rates and fecundities. At death, a mosquito's insemination status and wing length were determined. These life‐history traits allowed incorporation of larval dynamics into a vectorial capacity estimate. This new study provided both novel assemblages of putative host plants and a human blood host within a nocturnal period of maximum biting. Survivorship was significantly greater in nectar‐rich environments than nectar‐poor ones, resulting in greater total fecundity. Daily biting rate and fecundity per female between treatments was not detected. These results translated to greater estimated vectorial capacities in the nectar‐rich environment in all four replicates of the experiment (means: 1, 089.5 ± 125.2 vs. 518.3 ± 60.6). When mosquito density was made a function of survival and fecundity, rather than held constant, the difference between plant treatments was more pronounced, but so was the variance, so differences were not statistically significant. In the nectar‐poor environment, females' survival suffered severely when a blood host was not provided. A sugar‐accessibility experiment confirmed that Parthenium hysterophorus is a nectar‐poor plant for these mosquitoes. Synthesis and applications . This study, assessing the effect of particular plant species assemblages on the vectorial capacity of malaria mosquitoes, highlights the likelihood that changes in plant communities (e.g. due to introduction of exotic or nectar‐rich species) can increase malaria transmission and that a reduction of favourable nectar sources can reduce it. Also, plant communities' data can be used to identify potential high risk areas. Further studies are warranted to explore how and when management of plant species assemblages should be considered as an option in an integrated vector management strategy. Abstract : This study, assessing the effect of particular plant species assemblages on the vectorial capacity of malaria mosquitoes, highlights the likelihood that changes in plant communities (e.g. due to introduction of exotic or nectar‐rich species) can increase malaria transmission and that a reduction of favourable nectar sources can reduce it. Also, plant communities' data can be used to identify potential high risk areas. Further studies are warranted to explore how and when management of plant species assemblages should be considered as an option in an integrated vector management strategy.